The Influence of the Principal's Democratic Leadership Style and Teachers' Work Culture on Teacher Performance in Public Elementary School Clusters I and II, Pagaran District - Pretti Sihombing; Lustani Samosir; Arip Surpi Sitompul (Sean Institute, 2026)
Teacher performance is one of the key factors determining the quality of education. However, preliminary observations conducted at Cluster I and Cluster II Public Elementary Schools in Pagaran District revealed low teacher work motivation, limited instructional innovation, and inadequate participation in Teacher Working Group (Kelompok Kerja Guru/KKG) activities. These conditions are presumed to be influenced by the democratic leadership style of school principals and teachers' work culture. This study aimed to analyze the effect of the principals' democratic leadership style on teacher performance, the effect of teachers' work culture on teacher performance, and the simultaneous effect of both variables on teacher performance in Cluster I and Cluster II Public Elementary Schools in Pagaran District. This study employed a quantitative approach with an associative research design. The population consisted of 91 teachers, all of whom were selected as the research sample using the total sampling technique. Data were collected through closed-ended questionnaires based on a Likert scale and analyzed using descriptive statistics, classical assumption tests, simple and multiple linear regression analyses, correlation analysis, coefficient of determination analysis, and hypothesis testing. The results revealed that the principals' democratic leadership style had a positive and significant effect on teacher performance, with a coefficient of determination of 22.3% (F = 25.560; p < 0.05). Teachers' work culture also had a positive and significant effect on teacher performance, with a coefficient of determination of 29.1% (F = 36.560; p < 0.05). Simultaneously, the principals' democratic leadership style and teachers' work culture had a positive and significant effect on teacher performance, with a correlation coefficient (R) of 0.566, a coefficient of determination of 32.0%, and an F-value of 20.714 (p < 0.05). These findings indicate that better implementation of a democratic leadership style by school principals and a stronger teachers' work culture contribute to improved teacher performance.